PENGANGGARAN PARTISIPATIF SEBAGAI MOTIVASI KINERJA MANAJER - HARIYANTO, EKO (Jurnal Ilmiah Akuntansi dan Bisnis, 2010)
Researches about effects of participative budget on manager’s performance have been undertaken considerably. However, the results of which have been conflicting. This is due to the differences in the intervening and moderating variables used. The issue of whether higher levels of participative budget enhance managers’ performance has been widely studied in the accounting literature. Current empirical findings, however, have shown that it has indirect relationship, suggesting that budgetary participation does not have influence manager’s performance, but rather is conditioned on other intervening variables. This study aims, first, to examine the effect of participative budget on manager’s performance, and to examine the indirect effect of goal commitment and motivation as intervening variable. Second, it aims to examine the effect of leadership style as a moderating variable in the relationship between participative budget and goal commitment. The data collected by survey questionnaires. One hundred and fifteen middle level managers, who were randomly chosen from state owned enterprises in Indonesia, are participated in this research. Partial least Square (PLS) to run a structural equation modeling (SEM) technique was employed to analyze the data. The finding showed that participative budget does not significantly influence manager’s performance. Participative budget increases the managers’ performance through the increase of goal commitment, which has a significant, positive effect on motivation. Furthermore motivation also has a significant, positive effect on managers’ performance. Leadership style moderates the relationship between participative budget and goal commitment.
Keywords: participative budget, goal commitment, leadership style, motivation, manager performance, goal setting theory, moderating variable, intervening variable, state owned enterprise.